Regional cerebral blood flow in IDDM patients: effects of diabetes and of recurrent severe hypoglycaemia. - MacLeod, K; Hepburn, D; Deary, I; Goodwin, G; Dougall, N; Ebmeier, K; Frier, B (1994)
Chronic hyperglycaemia and recurrent severe hypoglycaemia have both been implicated as causing cerebral damage in patients with diabetes. Although cognitive dysfunction and intellectual impairment have been demonstrated in patients with recurrent severe hypoglycaemia, structural correlates have not been described, and it is not known whether specific functional changes occur in the brains of affected patients. Regional cerebral blood flow was estimated by SPECT with 99mTechnetium Exametazime in 20 patients with IDDM. Ten patients had never experienced severe hypoglycaemia and 10 had a history of recurrent severe hypoglycaemia. Patient results were compared with 20 age- and sex-matched healthy volunteers. We observed differences between the two patient groups and the control group. Tracer uptake was greater in diabetic patients in the superior pre-frontal cortex. This effect was particularly pronounced in the group who had a history of previous severe hypoglycaemia. Patients with a history of recurrent hypoglycaemia also had a relative reduction in tracer uptake to the calcarine cortex. This suggests an alteration in the pattern of baseline regional cerebral blood flow in diabetic patients with frontal excess and relative posterior reduction in cerebral blood flow.